Investigating EFL students’ linguistic problems using Grammarly as automated writing evaluation feedback - Anna Riana Suryanti Tambunan; Widya Andayani; Winda Setia Sari; Fauziah Khairani Lubis (Indonesian Journal of Applied Linguistics, 2022)
A plethora of previous studies has shown that corrective feedback can benefit students to progress in their learning. Due to technological advancement, there is a need to investigate the profile of corrective feedback to students’ writing via automated writing evaluation (AWE), particularly in the Indonesian higher education context. Therefore, this research aims to employ an AWE platform, Grammarly, to investigate the Indonesian English as a foreign language (EFL) students’ writing profiles in spelling, grammar, punctuation, enhancement suggestion, sentence structure, and style check. This ex post facto study explored the assignment written by 54 fourth-semester English department students enrolled in an academic writing course at an Indonesian university. The students’ writing profiles were classified, identified, and categorized using the Grammarly platform. Descriptive statistics were used to obtain the average, standard deviation, and significant differences according to the writing profiles between male and female students. The result stated that grammar is the major problem possessed by students. Furthermore, teachers are expected to provide online corrective feedback for students in the Academic Writing course learning process.